Financial leverage in manufacturing sector in Malaysia / Nur Shafiera Aspal Anawal - Aspal Anawal, Nur Shafiera (Faculty of Business Management, 2017)
This research paper will investigate the financial leverage of manufacturing firms that are listed in Bursa Malaysia. The sample of the data covers ten of manufacturing firm for the ten years period from 2005 until 2015. Panel data is used for the analysis and the ordinary least square method (OLS) is also used to minimize the error in the estimation results. The primary objective of this research is to investigate the relationship between financial leverage towards capital structure in manufacturing firms in Malaysia. For this purpose, debt ratios is taken as dependent variable meanwhile profitability, tangibility, firm‟s size, growth and risk are taken as independent variables. The findings of this study shows tangibility, firm‟s size and growth has positive relationship towards debt ratios. Meanwhile, profitability and risk has negative relationship towards debt ratios.